Glacially-triggered faulting - Olesen, Odleiv; Steffen, Holger; Sutinen, Raimo (Cambridge University Press, 2022)
Glacially triggered faulting describes movement of pre-existing faults caused by a combination of tectonic and glacially induced isostatic stresses. The most impressive fault-scarps are found in northern Europe, assumed to be reactivated at the end of the deglaciation. This view has been challenged as new faults have been discovered globally with advanced techniques such as LiDAR, and fault activity dating has shown several phases of reactivation thousands of years after deglaciation ended. This book summarizes the current state-of-the-art research in glacially triggered faulting, discussing the theoretical aspects that explain the presence of glacially induced structures and reviews the geological, geophysical, geodetic and geomorphological investigation methods. Written by a team of international experts, it provides the first global overview of confirmed and proposed glacially induced faults, and provides an outline for modelling these stresses and features. It is a go-to reference for geoscientists and engineers interested in ice sheet-solid Earth interaction.